Job satisfaction of health professionals in a University Hospital: General analysis and job categories - Carrillo-García, César; Martínez-Roche, María E.; Gómez-García, Carmen I.; Meseguer-DePedro, Mariano (Anales de Psicología / Annals of Psychology, 2015)
Job satisfaction in health services is measured by the quality of care provided, hence the importance of surveying the workers of health institutions. The objective was to explore and analyze the phenomenon of the satisfaction of working in a sample made up of 546 health professionals belonging to a public University Hospital. Both a socio-demographic questionnaire and General Scale of Satisfaction (Overall Job Satisfacción) that were both validated in Spanish were given to the participants. The results of general satisfaction showed a mean of 71.37 (SD = 14.03). The subscales with better results were: colleagues and immediate superior. There were important differences in satisfaction scores between the different professional categories. The higher levels of general satisfaction were found in hospital management groups and resident doctors, while the lower levels of general satisfaction were found in medical area specialists, nurses and auxiliary nurses.